Identificação e prevalência de bactérias causadoras de infecções urinárias em nível ambulatorial (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2017)
Identification and prevalence of bacterial causes of urinary tract infections in an outpatient setting